MODUL PSEUDO PROYEKTIF KECIL (SMALL PSEUDO PROJECTIVE MODULES) - , JEINNE MUMU ([Yogyakarta] : Universitas Gadjah Mada, 2011)
An R-module M is called small pseudo projective modules if for any epimorfisme f: M A and small epimorfisme g: M A, there is h: M M such that f = g h. Small pseudo projective modules related is quasi-projective modules, small sub modules, small epimorfisme and stable sub modules. If M quasi projective modules then M small pseudo projective modules. This relationship will be valid on the contrary, if M is a hollow module. This paper discusses the small pseudo projective modules are constructed of quasi projective modules. Also discussed the properties of small sub modules, small epimorfisme and stable sub modules in small pseudo projective modules. Keywords: quasi projective modules, small pseudo projective modules, small sub modules, small epimorfisme and stable sub modules.